EXPLORING THE ROLE OF SOCIAL EXPERIENCE IN SHAPING SOCIAL ENTREPRENEURSHIP INTENTIONS AMONG GENERATION Z - Reinaldo Juan; Lydiawati Soelaiman (International Journal of Application on Economics and Business, 2026)
Social entrepreneurship addresses social problems and supports communities. This study aims to determine the effect of social experience on the intention to engage in social entrepreneurship with empathy, moral obligation, and perceived social support as mediating variables among Generation Z in West Jakarta. This study uses a descriptive, quantitative approach, purposive sampling and non-probability methods for sample selection. The sample in this study consists of Generation Z aged 20-27 years who have been involved in social activities and reside in West Jakarta. This study collected questionnaire data online via Google Forms and managed it using SmartPLS 4, version 4.1.1.4. The results of this study show that social experience has a significant, positive impact on empathy, moral obligation, and perceived social support. The study's results show that perceived social support has a substantial, positive effect on the intention to engage in social entrepreneurship. Meanwhile, empathy and moral obligation do not significantly impact on the intention to engage in social entrepreneurship. Additionally, the mediating variable of perceived social support can mediate the influence of social field experience on social entrepreneurship intentions. However, empathy and moral obligation variables cannot mediate the influence of social field experience on social entrepreneurship intentions. This research is expected to enhance knowledge in fostering social entrepreneurship among Generation Z.